Effects of surface nature of different semiconductor substrates on the plasma enhanced atomic layer deposition growth of Al2O3 gate dielectric thin films. Issue 7 (5th June 2015) - Schilirò, Emanuela; Greco, Giuseppe; Fiorenza, Patrick; Tudisco, Cristina; Condorelli, Guglielmo Guido; Di Franco, Salvatore; Roccaforte, Fabrizio; Lo Nigro, Raffaella; Hoffmann, Patrik; Knez, Mato; Vahlas, Constantin; Alexandrov, Sergei
Abstract In this work, we present a systematic study on the effects of surface nature of two different substrates such as Si(100) and AlGaN/GaN (0001) before atomic layer deposition (ALD) growth of Al2O3 thin films. The Si and AlGaN/GaN surfaces were treated either with: H2O2:H2SO4 (1:3 piranha solution) for 10 minutes and H2O:HF (10:1) for 5 minutes. After surface pretreatment, Al2O3 was immediately deposited at 250 °C by Plasma Enhanced ALD from trimethylaluminum precursor. The film thicknesses were measured to be 28 nm using transmission electron microscopy and different structural evolution has been observed under electron beam analysis, rearraging from amorphous as‐deposited films to epitaxial films depending on the substrate type. Surface morphology obtained by atomic force microscopy in tapping mode shows scattered three‐dimensional nucleation of Al2O3 thin films on Si(001) substrate, while deposition on AlGaN/GaN(0001) resulted in smooth Al2O3 layers. Moreover, X‐ray photoelectron spectroscopy investigation demonstrated a different interfacial interaction between the Al2O3 films and the two different substrates. However, analogous dielectric properties have been evaluated for both films deposited on the two Si(100) and AlGaN/GaN (0001) substrates. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)